Introduksi Sistem Aplikasi STUNNING bagi MGMP di Lingkungan Dinas Pendidikan Provinsi Jawa Timur - Bambang Hariadi; Edo Yonatan Koentjoro; Pradita Maulidya Effendi; Erwin Soetomo; Julianto Lemantara; M.J. Dewiyani Sunarto (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to introduce STUNNING as a tool for evaluating high school student learning-based information technology. The method for implementing this service activity uses seminars, which are part of a series with the Opening of the 2023 Matching Fund Activities at Dinamika University. This activity was attended by 45 participants from subject teachers who were members of the MGMP administrators within the East Java Provincial Education Office and attended by several media crews, including D'Media, BTV, MNCTV, Merro, and Analisapost.com. The evaluation instrument for this activity uses a questionnaire, which is then analyzed descriptively. The results of this service show that the introduction of the STUNNING application system has been successfully implemented and can achieve the stated goals. Participants seemed enthusiastic and welcomed the presence of STUNNING to evaluate learning for high school students. This is also reinforced by the results of the participant questionnaire, which shows an average score of 3.63 from a range of 1-4 scores.